Continuously Paranoid Schizophrenia in Young Man: A Case Report - Era Catur Prasetya; Roni Subagyo; Muhammad Hanun Mahyuddin; Ulaa Haniifah; Maya Rafida; Anisatul Hamida; Muhammad Ramzy; Muhammad Tegar Prasetya (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2022)
Introduction: Schizophrenia is a chronic disorder accompanied by prominent hallucinations or delusions. The individual must be ill for at least 6 months and need not be psychotically active during that time. Schizophrenia is classified into several types. Enforcement of the type of diagnosis of schizophrenia can be established through history taking in the patient and family, then a diagnosis is made according to ICD-10. Treatment can be in the form of pharmacological or psychosocial therapy. Case Reports: A 32-year-old male patient came with his family, the patient looked anxious. The patient comes with the main complaint that he is often angry because he often hears voice whispers. The patient also complains of rapid mood changes. According to the family, this has been happening since 2015. He had been on treatment for a while but only got better shortly after that it came back again. Conclusion: Schizophrenia is a psychotic disorder in which the patient does not have contact with reality which is characterized by major disturbances in thoughts and emotions and experiences delusions and hallucinations. Schizophrenia can be treated using antipsychotics and psychosocial. The prognosis of patients with schizophrenia depends on family support.